Disentangling the correlated evolution of body size, life history, and ontogeny in miniaturized chelydroid turtles. Issue 5 (26th May 2021) - Cordero, Gerardo A.
Abstract: Organismal miniaturization is defined by a reduction in body size relative to a large ancestor. In vertebrate animals, miniaturization is achieved by suppressing the energetics of growth. However, this might interfere with reproductive strategies in egg‐laying species with limited energy budgets for embryo growth and differentiation. In general, the extent to which miniaturization coincides with alterations in animal development remains obscure. To address the interplay among body size, life history, and ontogeny, miniaturization in chelydroid turtles was examined. The analyses corroborated that miniaturization in the Chelydroidea clade is underlain by a dampening of the ancestral growth trajectory. There were no associated shifts in the early sequence of developmental transformations, though the relative duration of organogenesis was shortened in miniaturized embryos. The size of eggs, hatchlings, and adults was positively correlated within Chelydroidea. A phylogenetically broader exploration revealed an alternative miniaturization mode wherein exceptionally large hatchlings grow minimally and thus attain diminutive adult sizes. Lastly, it is shown that miniaturized Chelydroidea turtles undergo accelerated ossification coupled with a ~10% reduction in shell bones. As in other vertebrates, the effects of miniaturization were not systemic, possibly owing to opposing functional demands and tissue geometric constraints. This underscores the integrated and hierarchical nature of developmental systems. Abstract : Descendant–ancestor relationships in the evolution of body size miniaturization, as exemplified by chelydroid turtles. Research Highlights: This study describes two modes of miniaturization in turtles with diverse life histories: (i) "grow slowly and stay small"; (ii) "grow large early but reduce growth later." In the former, the ancestral growth trajectory is stifled. These miniaturized turtles generally retain the ancestral developmental sequence but undergo changes in the number and maturity of shell bones. Miniaturization entails a mosaic of alterations that are subject to opposing selective pressures.